LEGAL DIALECTICS OF INTERNATIONAL REFUGEE MIGRATION DETERMINATION IN INDONESIA - M. Alvi Syahrin; Pramella Y. Pasaribu (Jurnal Ilmiah Kajian Keimigrasian, 2018)
Indonesia is not a state party to the 1951 Convention. There are no rights and obligations attached to Indonesia for the problem of asylum seekers and seekers. Their existence will be caused by community culture. The research method used is a normative legal approach by analyzing various laws in order to get a clear answer. Based on the results of the discussion, income is referred to as follows. (i) The existence of refugees and asylum seekers in Indonesia has a negative impact on the social conditions of the Indonesian people, in the form of illegal marriages, unclear children's status, children losing civil rights. In addition, refugees often create chaos in the community, due to differences in language and culture. (ii) Legal efforts made by the Directorate General of Immigration in matters and solutions by Government Regulation Number IMI-1489.UM.08.05 of 2010 concerning Handling of Illegal Immigrants and continuing to coordinate with UNHCR for resettlement to third countries.